COVID-19 and Preeclampsia - Celi Castro, Adriana Lucía (2023)
Despite the decline in maternal deaths, COVID-19 and preeclampsia remain the leading causes. Both have a similar pathophysiology and therefore similar symptoms and laboratory. For this reason, prenatal control is necessary not only for preeclampsia but also for COVID-19. Likewise, it is necessary to investigate its causality.